DINAMIKA IMBIBISI BENIH BUNCIS (Phaseolus vulgaris L.) SELAMA PERENDAMAN DALAM AQUADES - Nurfiana, Yuni; Rais, M. Amien; Nuraisyah, Anni (Institute of Computer Science (IOCS), 2025)
This study aimed to determine the imbibition rate of bean seeds (Phaseolus vulgaris L.) through soaking in distilled water (aquades) for 32 hours. The imbibition process was observed by measuring the seed weight every two hours using a digital scale. A total of 25 seeds were used for each replication, with five replications conducted. The results showed that water uptake occurred rapidly during the first 8 hours and then slowed down and showed no further imbibition activity until the 32nd hour. The data revealed a characteristic imbibition curve pattern, providing valuable insights for pre-sowing seed treatment to enhance germination efficiency. This research is important to determine how long farmers should soak seeds before planting to achieve optimal germination while preventing excessive soaking that may cause seed rot.